Accuracy of Individuals Post-hemiparetic Stroke in Matching Torques Between Arms Depends on the Arm Referenced - Gurari, Netta; van der Helm, Nina A.; Drogos, Justin M.; Dewald, Julius P. A. (Frontiers in Neurology, 2019)
Background. Prior work indicates that 50-75% of individuals post-hemiparetic stroke have upper-extremity weakness and, in turn, inaccurately judge the relative torques that their arms generate during a bimanual task. Recent findings also reveal that these individuals judge the relative torques their arms generate differently depending on whether they reference their paretic versus non-paretic arm. Objective. Our goal was to determine whether individuals with hemiparetic stroke inaccurately matched torques between arms, regardless of the arm that they referenced. Methods. Fifteen participants with hemiparetic stroke and ten right-hand dominant controls matched torques between arms. Participants performed this task with their right arm referencing their left arm, and vice versa. Participants generated 1) 5Nm and 2) 25% of their reference elbow’s maximum voluntary torque (MVT) in flexion and extension using their reference arm while receiving audiovisual feedback. Then, participants matched the reference torque using their opposite arm without receiving feedback on their matching performance. Results. Participants with stroke had greater magnitudes of error in matching torques than controls when referencing their paretic arm (p<0.050), yet not when referencing their non-paretic arm (p>0.050). The mean magnitude of error when participants with stroke referenced their paretic and non-paretic arm and controls referenced their dominant and non-dominant arm to generate 5Nm in flexion was 9.4Nm, 2.6Nm, 4.2Nm, and 2.5Nm, respectively, and in extension was 5.3Nm, 2.8Nm, 2.5Nm, and 2.3Nm, respectively. However, when the torques generated at each arm were normalized by the corresponding MVT, no differences were found in matching errors regardless of the arm participants referenced (p>0.050). Conclusions. Results demonstrate the importance of the arm referenced, i.e., paretic versus non-paretic, on how accurately individuals post-hemiparetic stroke judge their torques during a bimanual task. Results also indicate that individuals with hemiparetic stroke judge torques primarily based on their perceived effort. Finally, findings support the notion that training individuals post-hemiparetic stroke to accurately perceive their self-generated torques, with a focus of their non-paretic arm in relation to their paretic arm, may lead to an improved ability to perform bimanual activities of daily living.